Illegal hunting cases detected with molecular forensics in Brazil - Sanches, Alexandra [UNESP]; Tokumoto, Paola M. [UNESP]; Peres, Wellington A.M.; Nunes, Fernando L.; Gotardi, Mariana S.T. [UNESP]; Carvalho, Carolina S. [UNESP]; Pelizzon, Cristiane [UNESP]; Godoi, Tamissa G. [UNESP]; Galetti, Mauro [UNESP] (Springer Nature, 2012)
Background: Illegal hunting is one of the major threats to vertebrate populations in tropical regions. This unsustainable practice has serious consequences not only for the target populations, but also for the dynamics and structure of tropical ecosystems. Generally, in cases of suspected illegal hunting, the only evidence available is pieces of meat, skin or bone. In these cases, species identification can only be reliably determined using molecular technologies. Here, we reported an investigative study of three cases of suspected wildlife poaching in which molecular biology techniques were employed to identify the hunted species from remains of meat.Findings: By applying cytochrome b (cyt-b) and cytochrome oxidase subunit I (COI) molecular markers, the suspected illegal poaching was confirmed by the identification of three wild species, capybara (Hydrochoerus hydrochaeris), Chaco Chachalaca (Ortalis canicollis) and Pampas deer (Ozotoceros bezoarticus). In Brazil, hunting is a criminal offense, and based on this evidence, the defendants were found guilty and punished with fines; they may still be sentenced to prison for a period of 6 to 12 months.Conclusions: The genetic analysis used in this investigative study was suitable to diagnose the species killed and solve these criminal investigations. Molecular forensic techniques can therefore provide an important tool that enables local law enforcement agencies to apprehend illegal poachers. © 2012 Sanches et al.; licensee BioMed Central Ltd.
Keywords: Bush meat; mtDNA; Neotropical region; Poaching; Species identification; Wildlife forensics; cytochrome b; cytochrome c oxidase; cytochrome oxidase subunit I; genomic DNA; unclassified drug; animal hunting; Brazil; chicken; criminal law; deer; DNA sequence; forensic identification; genetic analysis; genetic distance; Hydrochoerus hydrochaeris; law enforcement; mammal; meat; nonhuman; nucleotide sequence; Ortalis canicollis; Ozotoceros bezoarticus; priority journal; prison; punishment; sequence alignment; sequence analysis; species identification; unindexed sequence; wildlife; Agonidae; Hydrochaeris hydrochaeris; Vertebrata